A DIFFERENTIATED SURGICAL APPROACH IN ACUTE PANCREATITIS: OUTCOME PREDICTION AND TREATMENT OPTIMIZATION (Лучшие интеллектуальные исследования, 2025)
Background:Acute pancreatitis (AP) is a life-threatening abdominal emergency with increasing incidence and significant morbidity and mortality. Severe forms often involve necrotizing pancreatitis, with up to 30–70% mortality in infected cases. Current surgical approaches remain controversial, particularly in choosing between open and minimally invasive techniques during different disease phases. This study aimed to develop and evaluate a differentiated, evidence-based surgical strategy to improve outcomes in patients with severe AP.